227k views
4 votes
Need help solving this step by stepY = 2x x = 2y - 2

User ViKi Vyas
by
5.2k points

1 Answer

3 votes

equation 1) Y = 2x

Eq 2) x = 2y - 2​

1. First we need to replace Y from eq1 into Eq2,

x = 2 y - 2

X = 2 (2X) - 2

2. Now let's solve for x

X = 4X - 2

X - 4X = -2

- 3X = - 2

3X = 2

X = 2/3

we have found X = 2/3,

3. Let's replace the value of X we have found into equation 1

Y = 2 X

Y = 2 (2/3)

Y = 4 /3

Thus, X = 2/3 and Y = 4/3

User Immorality
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.